The Penaincisalia amatista species-group (Lepidoptera: Lycaenidae, Eumaeini) in Colombia, insights from mtDNA barcodes and the description of a new species. Issue 2 (3rd March 2016) - Prieto, Carlos; Grishin, Nick V.; Hausmann, Axel; Lorenc-brudecka, Jadwiga
Abstract : A synopsis of the P. amatista species-group in Colombia is provided. Five taxa are considered valid at species level, male and female phenotypes are associated, diagnosed and data on their distribution are given. The geographic variability of the species is discussed, and Penaincisalia celosia new species is described from specimens collected in an isolated branch of the central range in Colombian Andes. We present evidence to consider P. galeraensis (Salazar, Schmidt-Mumm, & Johnson) as a junior synonym of P. albalineata (Johnson). DNA barcodes provided additional information, which was in perfect agreement with the external characters in two of the five species. Interspecific distances were found to range from 0.6% to 6.6% (average 4.3), whilst their mean intraspecific variation ranges from 0.0% to 3.3% (average 0.7%).